Current mirror‐based compensation circuit for multi‐row read in‐memory computing. Issue 22 (1st October 2019) - Lin, Zhiting; Fang, Yaqi; Peng, Chunyu; Lu, Wenjuan; Li, Xuan; Wu, Xiulong; Chen, Junning
Abstract : Multi‐row read plays an important role in in‐memory computing and its precision affects the accuracy of the calculation. In this brief Letter, a discharge compensation method is proposed for the linearisation of multi‐row read operations in static RAM. Current mirrors are added to bitlines to compensate for the discharge voltage. With compensation, the integral non‐linearity decreases by 72% compared with the situation without compensation. In addition, a wordline signal generation circuit based on replica bitline is proposed to reduce area cost.